Uji Aktivitas Antibakteri Ekstrak dan Fraksi n-Heksan, Etil Asetat, Air Kulit Buah Naga Putih (Hylocereus Undatus) Terhadap Staphylococcus Epidermidis ATCC 12238 - Muhammad Abdul Azis; Tatiana Siska Wardani; Anna Fitriawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Research on the antibacterial test of dragon fruit peel extract carried out by Anggraini & Harris (2017) shows that white dragon fruit extract is able to inhibit the growth of epidermal Staphylococcus bacteria with the lowest concentration, namely 25%, producing an average diameter of the inhibition zone of 13.7 mm, while for the highest concentration, namely 100%, it produces an average diameter of the inhibition zone of 17.7 mm. To determine the more effective antibacterial effect of white dragon fruit peel extract, the research continued to the fractionation stage to separate compounds based on polarity level. The solvents used are water which is a polar solvent, ethyl acetate which is a semi-polar solvent, and n-hexane which is a nonpolar solvent (Yohanes, 2020). Based on the description above, researchers are interested in conducting research on testing the antibacterial activity of ethanol extract and n-hexane fraction of white dragon fruit peel (Hylocereus undatus) against Staphylococcus epidermidis bacteria.